(untitled) (Lafia Journal of Scientific and Industrial Research, 2026)
Due to the challenges faced by most electrolytes in withstanding high temperatures especially during peak operating conditions, this study analyses the thermal stability of cassava starch-polyvinylpyyrrolidone nanocomposite polymer electrolytes for lithium-ion battery applications. The study employed five samples of cassava starch-polyvinylpyyrrolidone nanocomposite polymer electrolytes prepared using direct-heating solution casting method. The data collected from these samples were analyzed using Bragg’s. Sherrer’s and Kissinger models. The results showed that all the samples are within the medium crystallite size and moderate thermal stability range,w with Sample 5 having the highest peak decomposition temperature and thermal stability of 194KJ/mol.